KAJIAN YURIDIS PENEGAKAN HUKUM PERJUDIAN ONLINE (Studi Kasus Putusan Pengadilan Negeri Sumber Nomor 277/Pid.B./2018/PN.Sbr) - TRIWIRATNO, BAMBANG (Dinamika Hukum, 2019)
The purpose of this research is to study and analyse the legal arrangements of online gambling criminal acts in Indonesia. Reviewing and analyzing criminal liability against perpetrators of online gambling crimes at the decision of the state court of Source No. 277/Pid. B./2018/PN.Sbr. Review and analyse barriers in the online gambling proving associated with Law No. 19-year 2016 concerning amendment to law No. 11 year 2008 on information and electronic transactions. The method of approach in writing is normative juridical, the nature of this research is analytical descriptive research. The data source uses secondary data. Data collection techniques using literature study/document study. Data analysis techniques use a qualitative descriptive approach. Based on the results of the research the discussion came to the conclusion that the criminal liability against the perpetrators of online gambling at the state court of Source No. 277/Pid. B./2018/PN. SBR of the defendant proved legally and assured Guilty of committing a criminal offence using gambling opportunities held in breach of article 303, and sentenced the imprisonment against defendant BUDIONO als BUDI Bin DAMIANTO, with imprisonment for 6 (six) months. Based on the results of the case analysis shows that the application of gambling acts through Internet facilities (online), only subject to the provisions of the law contained in the criminal CODE in this case article 303 CRIMINAL code. In fact, there has been a legal provisions governing gambling through Internet facilities (online) in article 27 paragraph (2) and article 45 paragraph (1) of the ITE LAW. It does not have the ITE LAW applied to the above cases, due to the investigation procedure in article 43 paragraph (6) of the ITE LAW which is difficult to implement. The difficult procedure is the provision that requires investigators to conduct arrest and detention, through the public Prosecutor requesting the determination of the Chairman of the local Court within 1x24 hours hours (one time twenty-four hours), Impossible to do so. Barriers to the online gambling proving associated with law No. 19 year 2016 about the amendment to law No. 11 year 2008 on information and electronic transactions can be viewed through the legal system either through legal factors, enforcement facilities, and society and culture. Keywords: Online Gambling, criminal liability, criminal offence proof.